Motivational Immediacy : Fostering Engagement in Adult Learners. - Taylor, Jonathan E. (Stylus Publishing, LLC, 2021)
This book provides a fresh look at the question of learner motivation and engagement, beginning with an investigation of potential motivations not to learn, the better to help instructors find more successful ways to engage learners in any given situation.